KARAKTERISTIK MORFOLOGI DAN AKTIVITAS ENZIM PROTEASE BAKTERI SIMBION NUDIBRANCH - Sabrina I Hengkengbala; Rosita AJ Lintang; Deiske A sumilat; Remy EP Mangindaan; Elvy Like Ginting; Sipriana Tumembouw (Sam Ratulangi University, 2021)
One type of enzyme whose application is very widespread is protease enzymes. Microorganisms that have not been widely explored as a source of protease enzymes are bacteria that are in conjunction with Nudibranch. The study aims to identify the morphological characteristics of bacteria, then determine the hydrolysis ability of protease enzymes from bacteria symbiont Nudibranch. Identification of morphological characteristics is done macroscopic, and microscopic with gram staining. Proteolytic activity tests are performed qualitatively by measuring the proteolytic index of bacteria grown on Skim Milk Agar medium. The results of macroscopic identification of symbiotic bacteria with Nudibranch are dominated by irregular colony shapes, undulated edges, growth of the entire colony has a flat height, milky white colony color, buttery texture and opaque bacterial colonies. Based on microscopic identification, two gram-negative isolates are obtained, namely RL.S14, S1.1.1, and gram positive isolates, namely AK.S00, AK.S01, AK.S02, AK.S03, S.PP1, RL.S6, S2.1.5, S2.2.1, S3.3.1, S3.3.4, RL.S10. Nudibranch symbiont Bacterial has colony cells were dominated by the diplobacillus form. The results of the protease activity test of Nudibranch symbiont bacteria showed that 12 positive isolates had proteolytic activity with the highest proteolytic index produced by isolate AK.S00, which was 2.5 mm.Â Keywords: Nudibranch, symbiotic bacteria, characteristics, protease